2020
DOI: 10.13104/imri.2020.24.2.76
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vendor-Provided Volumetry Software and NeuroQuant Using 3D T1-Weighted Images in Subjects with Cognitive Impairment: How Large is the Inter-Method Discrepancy?

Abstract: Background: Determination of inter-method differences between clinically available volumetry methods are essential for the clinical application of brain volumetry in a wider context. Purpose: The purpose of this study was to examine the inter-method reliability and differences between the Siemens morphometry (SM) software and the NeuroQuant (NQ) software. Materials and Methods: MR images of 86 subjects with subjective or objective cognitive impairment were included in this retrospective study. For this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
8
0
1
Order By: Relevance
“…However, in our study, the pallidum showed good reproducibility, which supports the assumption that the low reproducibility is due to a different atlas being used by each software program. 33 …”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the pallidum showed good reproducibility, which supports the assumption that the low reproducibility is due to a different atlas being used by each software program. 33 …”
Section: Discussionmentioning
confidence: 99%
“…이를 바탕으로 2018년 11월 20일 권고안 초안을 KSNR 집담회에서 중간보고하였으며, 2019년 전문위원회를 중심으로 진행한 연구 결과를 추가하고, 2018년 7월부터 2020년 6월까지의 관련 문헌 5건을 추가하여, 권고안을 최종적으로 수정 정리하였다( 9 10 11 12 13 ).…”
Section: 연구 방법unclassified
“…NeuroQuant V R generally has been found to have good to excellent reliability with FreeSurfer by our group, 33,34 and others. 30,35,40,74 Given the multiple studies showing good intermethod reliability and other types of reliability for NeuroQuant V R , 8,75,76 we believe that it is likely that the results of the current study would show good reliability with results from studies using programs like FreeSurfer. Nevertheless, it will be important to test this idea directly.…”
Section: Limitationsmentioning
confidence: 73%